Mitigating Long-term Unemployment in Europe - Miyamoto Hiroaki (Sciendo, 2021)
While unemployment rates in Europe declined after the global financial crisis until 2018/2019, the incidence of long-term unemployment, the share of people who have been unemployed for >1 year to the total unemployed, remained high. Moreover, the COVID-19 pandemic could aggravate the long-term unemployment. This paper explores the factors associated with long-term unemployment in European countries using a panel of 25 European countries over the period 2000–2018. We find that skill mismatches, labor market matching efficiency, and labor market policies are associated with the incidence of long-term unemployment. Among the different types of active labor market policies, training and startup incentives are found to be effective in reducing long-term unemployment.